2006
DOI: 10.1136/hrt.2005.086736
|View full text |Cite
|
Sign up to set email alerts
|

Hospital volume of throughput and periprocedural and medium-term adverse events after percutaneous coronary intervention: retrospective cohort study of all 17 417 procedures undertaken in Scotland, 1997-2003

Abstract: Objective: To determine whether percutaneous coronary intervention (PCI) hospital volume of throughput is associated with periprocedural and medium-term events, and whether any associations are independent of differences in case mix. Design: Retrospective cohort study of all PCIs undertaken in Scottish National Health Service hospitals over a six-year period. Methods: All PCIs in Scotland during 1997-2003 were examined. Linkage to administrative databases identified events over two years' follow up. The risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…The relationship of these outcomes and operator or institutional volume has not been shown earlier. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]35 Our study demonstrates a statistically significant inverse association between operator volume and outcome (in-hospital mortality and peri-procedural complications) in the current practice. Our results are in agreement with results from previous studies done both in the percutaneous transluminal coronary angioplasty and the stent era.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The relationship of these outcomes and operator or institutional volume has not been shown earlier. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]35 Our study demonstrates a statistically significant inverse association between operator volume and outcome (in-hospital mortality and peri-procedural complications) in the current practice. Our results are in agreement with results from previous studies done both in the percutaneous transluminal coronary angioplasty and the stent era.…”
mentioning
confidence: 59%
“…Our results are in agreement with results from previous studies done both in the percutaneous transluminal coronary angioplasty and the stent era. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]35,36 Previous studies have been limited by the number of centers, 12,20 state-based registry data, 8,14,15,18 inclusion of only limited cohorts, 16 lower sample size, 8,9,[11][12][13][14][15][16][17][18]20 foreign studies, 11,19,21 and most importantly they lack data from recent era. 6,7,9,16 Previous studies, which have shown a decrease in mortality with increasing operator volume, have failed to reach statistical significance because of low sample size, large confidence interval, or low procedure related mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is patients treated at high-volume hospitals encounter a lower risk of mortality when compared with patients treated at low-volume hospitals. But Burton et al (20) AMI -acute myocardial infarction, CHF -congestive heart failure, CI -confidence interval, COPD -chronic obstructive pulmonary disease, OR -odds ratio, , PCI -percutaneous coronary intervention (4) suggested that there is narrowing difference in mortality rates between high-and medium-volume hospitals due to accumulating experience with PCI procedures among surgeons, especially those serving in medium-PCI volume hospitals. In our study, crude 30-day mortality rate was 1.1% (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The published results from large real-world registries of usual practice indicate that the short-term risks are not negligible. (25,26) Patients and practitioners sometimes view PCI as a "holding" procedure, which delays CABG and there is a defi nite increase in the need for repeat revascularization, often by CABG, in patients initially treated by PCI. There is at least one observational study suggesting disturbingly that prior PCI may increase (double) in-hospital mortality after CABG.…”
Section: The Management Of Patients With Stable Coronary Syndromesmentioning
confidence: 99%